EFEKTIVITAS E-BOOK INTERAKTIF BERBASIS KEARIFAN LOKAL DALAM PEMBELAJARAN KETERAMPILAN MEMBACA TEKS BERITA KELAS VII SMP NEGERI 13 PADANG - Tri Vidya Rahmadhani; Amril Amir (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This research aims to evaluate the effectiveness of using interactive e-books based on local wisdom with a project based learning approach in learning news text reading skills in class VII students at SMP Negeri 13 Padang. This research uses a quantitative method with a quasi-experimental design involving two classes, namely an experimental class that uses interactive e-books and a control class that uses Ministry of Education and Culture books. Data was obtained through pretest and posttest tests which were measured using the N-Gain Score test. The research results showed that the average N-Gain Score for the experimental class reached 71.10%, which was included in the quite effective category, while the control class only reached 45.61%, which was in the moderate category. These findings indicate that interactive e-books based on local wisdom are more effective in improving students' reading skills compared to Kemendikbud books. The advantage of interactive e-books lies in the integration of multimedia elements and local wisdom which makes learning more interesting, contextual and relevant to students' lives. The PjBL approach also makes a significant contribution in training students' critical, analytical and collaborative thinking skills. This research recommends further development of digital-based learning media to support educational success in the modern era.